Upaya Pencegahan Keputihan Dengan Menerapkan Vaginal Hygine Pada Wanita Usia Subur Di PMB Imelda Tae Sekadau Tahun 2024 - Hearty Efifania Ose Payon (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The reproductive organs are one of the body's sensitive organs and require special care. Reproductive organ health starts with maintaining personal hygiene, including vaginal hygiene, which aims to ensure that the vagina remains clean, healthy, normal and free from disease. One of the reproductive health problems among women is vaginal discharge or known as Flour Albus (Wulan, 2019). Factors that cause vaginal discharge are physiological (normal) and pathological (abnormal) factors. Physiological factors (normal) vaginal discharge which are influenced by ovulation, before menstruation, intimate stimulation and emotions. On the other hand, pathological (abnormal) factors are caused by inflammation, germs, parasites, fungi and the Trichomonas vaginalis virus, vaginal bacteria, syfillis, candida albicans gonnorheae (Putri et al., 2015).